Engineering the Web in the Big Data Era : 15th International Conference, ICWE 2015, Rotterdam, The Netherlands, June 23-26, 2015, Proceedings - Cimiano, Philipp; Frasincar, Flavius; Houben, Geert-Jan.; Schwabe, Daniel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 15th International Conference on Web Engineering, ICWE 2015, held in Rotterdam, The Netherlands, in June 2015. The 26 full research papers, 11 short papers, 7 industry papers, 11 demonstrations, 6 posters and 4 contributions to the PhD symposium presented were carefully reviewed and selected from 100 submissions. Moreover 2 tutorials are presented. The papers focus on eight tracks, namely Web application modeling and engineering; mobile Web applications; social Web applications; semantic Web applications; quality and accessibility aspects of Web applications; Web applications composition and mashups; Web user interfaces; security and privacy in Web applications.
Web application modeling and engineering; mobile Web applications -- Social Web applications -- Semantic Web applications -- Quality and accessibility aspects of Web applications -- Web applications composition and mashups -- Web user interfaces -- Security and privacy in Web applications.
Keywords: Information storage and retrieva; Software engineering; Information systems; Computer science; Artificial intelligence; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Software Engineering; Computer Appl. in Administrative Data Processing; User Interfaces and Human Computer Interaction; Artificial Intelligence